Manajemen Pelayanan Perpustakaan dalam Meningkatkan Minat Baca Mahasiswa STIT Palapa Nusantara - Nasrullah (Pendidikan Al-Gafari, 2024)
The library is a means of learning that can be a force to educate the nation. Libraries have an important role as a bridge to the mastery of knowledge and a fun and refreshing place for recreation. Libraries make an important contribution to the disclosure of science information. Meanwhile, the library is the heart of academic activity, because with a library, data or information can be obtained which can be used as a basis for the development of knowledge. This research was carried out to 1) To find out how library services increase the interest and reading of STIT Palapa Nusantara students, 2) To find out the extent to which STIT Palapa Nusantara library services have increased interest in reading. This type of research is descriptive qualitative research. Data collection techniques use observation, interviews and documentation methods. The subjects of this research are the Head of the Library, and students of STIT Palapa Nusantara. The results of this research show that. From the entire series of data collection processes, the author draws several things that are facts about library services in increasing students' interest in reading at the Tarbiyah Palapa Nusantara College of Science, including the lack of attention from the school to improving library services, starting from the lack of book collections, inadequate facilities. adequate, library staff who are able to serve every visitor's needs, and poor library management processes by the head of the library have the effect of increasing students' reading interest in all forms of school library services. It is certain that this condition greatly influences students' interest in making the school library a one of the places to go when you need reading material or doing assignments.